Design And Fabrication Of Modular Fixture To Accommodate Flexible Assembly Systems - Abu Bakar, Md. Nazri (Universiti Sains Malaysia, 2005)
In the development of a modular fixture design system, it is essential to have a modular fixture specific information measurement that can be integrated with a CAD system, in addition to the other considerations such as fixture configuration, interference checking, etc., which are also important to fixture designers. The initial conditions for modular fixture assembly are established together with geometric relationships between fixture components and the workpiece to be analyzed. Of particular focus is the design of alternative locating points and components, together with examples of the 3-D fixture designs. Examples of fixture design generated by the system are also provided to illustrate the development. This thesis describes a method to create the fixture element database and model the fixturing towers like assembly of modular fixture. The main purpose for this project is to get the optimum of the modular fixture based on assembly process in order to make the product productivity and can reduce time in assembly and saving costs. The result in this case shows that the fixtures can be applied in many assembly situation such as assembly of 3-pin plug, optical mouse and alarm clock.